Peran Pendidikan Islam Sebagai Pilar Utama Dalam Membangun Sumber Perdamaian - Majdzub Muhammad Nabil (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Islamic education has an important role in teaching peace. In terms of language, Islam itself means peace, which is the term for the Arabic word silmun. Since its inception, Islam has always taught about peace, in spreading its beliefs, Islam has always used gentle methods of preaching, not forcing someone to follow Islamic teachings. Islamic education that starts from an early age has an important role in forming the character of an individual or society, so that individuals or society who have this character can widely spread peace. In practice, it is not easy for Islamic education to teach peace education, of course there are several obstacles that can disrupt the process of Islamic education teaching peace education.